EXISTING CONDITION OF GASTROPODS COMMUNITY IN COASTAL AREAS AFFECTED BY NICKEL OVERBURDEN IN POMALAA DISTRICT, SOUTHEAST SULAWESI PROVINCE, INDONESIA - Muhammad Purnama; Slamet Budi Prayitno; Max Rudolf Muskananfola; Suryanti Suryanti (BIOTROPIA, 2025)
ARTICLE HIGHLIGHT             The present investigation provides substantiated empirical evidence demonstrating that nickel extraction operations have exerted considerable detrimental effects on the ecological integrity of the Pomalaa coastal region in Southeast Sulawesi. Environmental degradation and disruption of ecological equilibrium have been observed as direct consequences of persistent overburden waste disposal. The introduction of mining overburden into the Pomalaa coastal ecosystem has resulted in the extirpation of critical gastropod taxa and significant population reductions among persisting species when compared with control sites featuring undisturbed substrate conditions. The documented diminished gastropod population densities within nickel mining-affected zones serve as biological indicators of profound environmental deterioration attributable to these industrial activities. ABSTRACT Pomalaa District is the largest existing nickel mining center in Southeast Sulawesi Province, Indonesia. Pollutants from various anthropogenic activities, especially nickel mining overburden, end up in the Pomalaa coastal area. This research aimed to determine the structure of the gastropods community in the impacted area and reference site. This research was carried out in the Pomalaa coastal area, Kolaka Regency, from June to October 2023. Research stations were determined using purposive sampling method and simple random sampling techniques. On-site collecting gastropods samples were carried out manually (handpicking method). Impacted area and reference site showed significant differences in the number of species (16 and 21 species), presence, and density of gastropods, even though their respective ecological index categories were relatively the same (H' = 1.92 & 2.72; R =  2.93 & 3.41; E  = 0.55 & 0.78; C = 0.001 & 0.04). In the impacted area, the density of gastropods was very low (1 - 3 ind./m2), whereas at the reference site, the density reached 10 - 30 ind./m2. Gastropods inhabiting rocks or hard substrates, were relatively unaffected by the overburden, proven by stable population with a high density of 45 - 115 ind./m2. Nickel overburden input flowing to the Pomalaa coastal area greatly influenced the gastropods community in terms of species composition and density. On the other hand, the habitat (substrate) of gastropods as benthic organisms was covered and degraded by overburden piles up to 15 - 30 cm deep, which  was still increasing over time. On the other hand, in the reference site area, the condition was inversely proportional.